Assessing emergency department nurses' ability to communicate with angry patients and the factors that influence it - Chen, Xi; Zeng, Yuting; Jiang, Ling; Tian, Lingyun; Yi, Jindong; He, Haiyan; Li, Fang; Long, Yanfang; Li, Li (Frontiers in Public Health, 2023)
Aims: To assess the emergency department (ED) nurses’ ability to communicate with angry patients, and to explore its influencing factors. Design: A cross-sectional survey design. Methods: This study was conducted in November-December 2020. Stratified sampling was adopted to recruit ED nurses from 18 tertiary hospitals in western, eastern, and central China to complete an online questionnaire. The Nurses' Communication Ability with Angry Patients Scale (NCAAPS) and the General Self-efficacy Scale (GSES) were used to assess ED nurses' communication ability and self-efficacy, respectively. The descriptive statistics, Mann - Whitney U test, Kruskal - Wallis H test, Spearman's correlation analysis, and the Generalized Linear Model were used for data analysis. Results: A total of 679 valid questionnaires were collected. The median age was 28 (IQR, 25-31) years, and 81.7% of respondents were women. The mean total score for the NCAAPS was 3.79 (SD = 0.47), while the scores for its four dimensions were 3.87 (SD =0.59) for communication skills, 3.82 (SD =0.59) for anger perception, 3.79 (SD =0.53) for self-preparation, 3.73 (SD =0.54) for exploring the cause of anger. A longer length of employment (β=0.02-0.04, p=0.04), previous training experience in communication ability (β=0.03, p=0.02), and higher self-efficacy (β=0.11, p<0.01) were significantly and independently associated with higher NCAAPS scores. Conclusions: There is still room for improvement in ED nurses’ ability to communicate with angry patients. Self-efficacy and training in communication skills are essential to improve ED nurses’ ability to communicate with angry patients. Impact: Findings of this study add important knowledge about the status and influencing factors of ED nurses’ communication ability with angry patients, thus providing evidence for developing intervention programs to improve such ability in the future.